Improving Torsional Behaviour Of Reinforced Concrete Beam Strengthened With Ultra High Performance Fibre Reinforced Concrete - Mohammed, Thaer Jasim (2016)
Reinforced concrete members subjected to torsion may fail suddenly due to insufficient transverse steel reinforcing resulting from construction errors, or increased loading due to a change in purpose. Therefore, strengthening and upgrading is the most cost-effective and convenient solution. The proposed techniques to strengthen concrete members such as steel plates, polymers or concrete have important deficiencies in adherence and durability. So, the use of ultra-high performance steel fibre concrete (UHPFC) can effectively resolve these problems. On the other hand, there have been very little studies on the torsional behaviour of reinforced concrete (RC) beams with UHPFC composite. This work aims at studying the strengthening of rectangular beams with or without stirrups using UHPFC with different types of configurations and thicknesses to improve the torsional resistance of RC beams. Thereby, an experimental study has been made through this investigation to understand the behaviour of RC beams with UHPFC under torsion. Moreover, simulation of the experimental beams was studied using finite element analysis. The FE method from the ANSYS program is used. Variables considered in the test program include; influence of UHPFC configuration (full, U-jacked and left-right sides), influence of UHPFC layer thickness (10, 15, 20 and 25 mm), and influence of transverse steel reinforcement. Test results are discussed in this research based on torque-twist behaviour, torque-strain curve, influence of UHPFC on cracking and ultimate torque, crack patterns and mode of failure of each beam. Results show that the UHPFC matrix can generally be used as an effective external torsional reinforcement for RC beams with or without stirrups. The UHPFC contribution to torsional strength is increased when thickness increases, for all cases of strengthened beams. Moreover, the UHPFC material can be cast in a thin layer, while sandblasting of the specimen surface ensures good adhesion of the U-jacket without using any primer, which subsequently prevents premature failure of the structure and a significant increase in torque capacity. Despite the positive effect in increasing the torque capacity, left-right wrappingis not the most efficient and economical scheme for strengthening reinforced concrete using UHPFC. The fully wrapped beams exhibited considerably higher torque capacity and torsional behaviour. Therefore, the cracking and maximum torque capacity of the strengthened beams is dependent on both configuration and volumetric ratios of UHPFC. Meanwhile, the FE results show good agreement with the experimental results. The ratio of experimental values of the cracking torque to the predicted valuesfrom the FE results for all beams hasa mean of 1.059 and standard deviation of 0.089.The ratio of experimental values of the maximum torque to the predicted values from the FE results for the beams has a mean of 1.038 and standard deviation of 0.062.It is worth mentioning, the possibility of increasing the durability of the member by applying the UHPFC matrix, due to the reduced crack openings and to the compactness of the UHPFC matrix. Hence, the use of UHPFC appears to be a good method to enhance the torsional performance of RC beams.